Rapid, reliable, and reproducible molecular sub-grouping of clinical medulloblastoma samples - Northcott, Paul A.; Remke, Marc; Kool, Marcel; Korshunov, Andrey; Pfister, Stefan (Acta neuropathologica, 2012)
The diagnosis of medulloblastoma likely encompasses several distinct entities, with recent evidence for the existence of at least four unique molecular subgroups that exhibit distinct genetic, transcriptional, demographic, and clinical features. Assignment of molecular subgroup through routine profiling of high-quality RNA on expression microarrays is likely impractical in the clinical setting. The planning and execution of medulloblastoma clinical trials that stratify by subgroup, or which are targeted to a specific subgroup requires technologies that can be economically, rapidly, reliably, and reproducibly applied to formalin-fixed paraffin embedded (FFPE) specimens. In the current study, we have developed an assay that accurately measures the expression level of 22 medulloblastoma subgroup-specific signature genes (CodeSet) using nanoString nCounter Technology.
Published online: 6 November 2011
Gesehen am 11.04.2018